ISH-guided freeze-matrix assisted punches: technique for extracting punches from thin slide-mounted tissues for DNA methylation analysis. (September 2012) - Own, Lawrence S.; Patel, Paresh D.
Dissection of discrete brain regions for molecular analysis is complicated by trade-offs between accuracy, flexibility, and costs. We developed a flexible and cost-effective method, in situ hybridization (ISH) guided freeze-matrix assisted punches (IFAP), for extracting nanogram quantities of DNA from slide-mounted sections as thin as 12 µm. Using ISH to localize regions of interest, tissue is targeted by applying a small bead of M-1 embedding matrix onto cryosections, snap-freezing, and collecting the beads for nucleic acid purification. The method quantitatively recovers RNA and DNA usable for PCR and DNA methylation analysis.